Can inorganic phosphate explain sag during unfused tetanic contractions of skeletal muscle?. Issue 22 (24th November 2016) - Smith, Ian C.; Bellissimo, Catherine; Herzog, Walter; Tupling, A. Russell
Abstract: We test the hypothesis that cytosolic inorganic phosphate (Pi ) can account for the contraction‐induced reductions in twitch duration which impair summation and cause force to decline (sag) during unfused tetanic contractions of fast‐twitch muscle. A five‐state model of crossbridge cycling was used to simulate twitch and unfused tetanic contractions. As Pi concentration ([Pi ]) was increased from 0 to 30 mmol·L −1, twitch duration decreased, with progressive reductions in sensitivity to Pi as [Pi ] was increased. When unfused tetani were simulated with rising [Pi ], sag was most pronounced when initial [Pi ] was low, and when the magnitude of [Pi ] increase was large. Fast‐twitch extensor digitorum longus (EDL) muscles (sag‐prone, typically low basal [Pi ]) and slow‐twitch soleus muscles (sag‐resistant, typically high basal [Pi ]) were isolated from 14 female C57BL/6 mice. Muscles were sequentially incubated in solutions containing either glucose or pyruvate to create typical and low Pi environments, respectively. Twitch duration was greater ( P  <   0.05) in pyruvate than glucose in both muscles. Stimuli applied at intervals approximately three times the time to peak twitch tension resulted in sag of 35.0 ± 3.7% in glucose and 50.5 ± 1.4% in pyruvate in the EDL (pyruvate > glucose; P  <   0.05), and 3.9 ± 0.3% in glucose and 37.8 ± 2.7% in pyruvate in the soleus (pyruvate > glucose; P  <   0.05). The influence of Pi on crossbridge cycling provides a tenable mechanism for sag. Moreover, the low basal [Pi ] in fast‐twitch relative to slow‐twitch muscle has promise as an explanation for the fiber‐type dependency of sag. Abstract : Fast‐twitch skeletal muscle commonly exhibits force declines (sag) when electrically stimulated at frequencies which produce unfused tetanic contractions, while slow‐twitch muscle is sag‐resistant. In this study we provide preliminary experimental and modeling evidence which suggests that accumulation of cytosolic inorganic phosphate concentration during contraction can abbreviate twitch duration to impair summation and facilitate sag. As this mechanism appears most effective in muscles with very low cytosolic phosphate concentrations at the onset of contraction (e.g., well rested fast‐twitch skeletal muscle), this may account for the fiber‐type dependent properties of sag.